Enantioselective electroreductive alkyne-aldehyde coupling - Xiyang Cao; Yuyang Fu; Yongsheng Tao; Qingquan Lu (Nature Communications)
Abstract Electrocatalytic methods that facilitate the asymmetric reductive coupling of two π-components with complete control over regio-, stereo-, and enantioselectivity remain underexplored. Herein, we report a highly regio- and enantioselective cobaltaelectro-catalyzed alkyne-aldehyde coupling reaction, in which protons and electrons serve as the hydrogen source and reductant, respectively. Earth-abundant cobalt and air-stable (S,S)−2,3-bis(tert-butylmethylphosphino)quinoxaline (QuinoxP*) are used as the catalyst and ligand, respectively. A series of enantioenriched allylic alcohols can be constructed with excellent regio- (>19:1), stereo- (>19:1 E:Z), and enantioselectivity (up to 98% ee).